Characteristics of Useful Code Reviews: An Empirical Study at Microsoft - Bosu, Amiangshu; Greiler, Michaela; Bird, Christian (Proceedings of the International Conference on Mining Software Repositories, 2015)
Over the past decade, both open source and commercial software projects have adopted contemporary peer code review practices as a quality control mechanism. Prior research has shown that developers spend a large amount of time and effort performing code reviews. Therefore, identifying factors that lead to useful code reviews can benefit projects by increasing code review effectiveness and quality. In a three-stage mixed research study, we qualitatively investigated what aspects of code reviews make them useful to developers, used our findings to build and verify a classification model that can distinguish between useful and not useful code review feedback, and finally we used this classifier to classify review comments enabling us to empirically investigate factors that lead to more effective code review feedback. In total, we analyzed 1.5 millions review comments from five Microsoft projects and uncovered many factors that affect the usefulness of review feedback. For example, we found that the proportion of useful comments made by a reviewer increases dramatically in the first year that he or she is at Microsoft but tends to plateau afterwards. In contrast, we found that the more files that are in a change, the lower the proportion of comments in the code review that will be of value to the author of the change. Based on our findings, we provide recommendations for practitioners to improve effectiveness of code reviews.